Laparoscopic transabdominal preperitoneal repair for female patients with groin hernias - Ronggui Lin; Xianchao Lin; Yuanyuan Yang; Congfei Wang; Haizong Fang; Yanchang Chen; Heguang Huang; Fengchun Lu (BMC, 2023)
Abstract Background Laparoscopic transabdominal preperitoneal repair (TAPP) was recommended for female patients with groin hernias. Whereas, only a few studies focused on whether and how to preserve the round ligament of the uterus in TAPP. Methods Clinical data of 159 female patients with 181 groin hernias who underwent TAPP at a single institution in China from January 2016 to June 2022 were retrospectively reviewed and collected. Results All the patients underwent the operation smoothly without conversion. Division of the round ligament was performed for 33 hernias. Preservation of the round ligament was adopted for 148 hernias, 51 with the "keyhole" technique, 86 with the "longitudinal incision of peritoneum" method, and 11 with total dissection of the round ligament. The mean operative time was 55.6 ± 8.7 min for unilateral TAPP and 99.1 ± 15.8 min for bilateral TAPP. The mean estimated blood loss was 7.1 ± 4.5 mL. The postoperative complications included 6 (3.3%) cases of seroma, 1 (0.5%) case of hematoma, and 3 (1.6%) cases of mild chronic pain. The incidences of chronic pelvic pain and genital prolapse seemed to be higher in the division group than in the preservation groups (6.1% vs. 0.6% and 3.0% vs. 0%, separately). However, no statistical difference was observed (p > 0.05). Conclusions TAPP is feasible and effective for female patients with groin hernias, especially in preserving the round ligament of the uterus.